National climate change impact assessments underestimate the potential of autonomous adaptation - Arbelaez-Gaviria, Juliana; Boere, Esther; Trnka, Miroslav; Havlik, Petr; Holman, Ian P.; Harrison, Paula A. (Springer, 2026)
Central Europe is projected to lose up to 25% of its crop productivity by 2050 because of climate change, posing significant challenges to agricultural systems and food security. Effective adaptation strategies must consider not only domestic impacts but also global climate effects, including international trade dynamics. We performed a multilevel analysis of climate change impacts on agriculture, using the Czech Republic, a landlocked, crop production-based economy with an open market, as a case study. We integrated the global biosphere management model (GLOBIOM) with the gridded global crop model EPIC-IIASA. Climate impacts were projected with five global circulation models under three climate scenarios, with and without CO2 fertilization, and applied in national, EU-regional, and global productivity change scenarios. The results show that national-only assessments underestimate both risks and opportunities: production is projected to decline by up to 9% when global interactions are excluded but to increase by up to 8% when trade and market effects are included. Autonomous adaptation mechanisms, such as cropland reallocation, shifts in management intensity, and trade adjustments, buffer biophysical yield losses and improve economic outcomes. Neglecting global interactions in national climate change assessments increases the risk of maladaptation and policy inefficiencies. The incorporation of international market linkages enhances the ability to design robust adaptation strategies, enabling countries such as the Czech Republic to maximize resilience while minimizing environmental and socioeconomic trade-offs.
Keywords: Climate change; Adaptation; Agricultural trade; Czech Republic; Integrated assessment; Food security; 3002 Agriculture, Land and Farm Management; 30 Agricultural, Veterinary and Food Sciences; 13 Climate Action; 2 Zero Hunger; Ecology